Українська жіноча література кінця XIX - початку XX століття та тема жінки у творчості Галини Комарівни - Ходюк, О. (Літературознавчі обрії. Праці молодих учених, 2010)
At the end of the XIX and the beginning of the XX century the Ukrainian nation makes more and more courageous steps to the full-valued life which helps to promote the development of the women’s consciousness. National and women’s problems are the main topics (in the creative works of women – members of the feminist movement, as women can be free only being independent) in an independent and free country. With her creative work Halyna Komarivna made a great contribution into the development of Ukrainian literature. Women’s theme became the most important in her creativity.